TEKS DAN KONTEKS DISKURSUS PERLAWANAN FRONT PEMBELA ISLAM (FPI) - Romdlon, Atiq M; Fidiyanti, Murni; Rohman, Abdur; Rosyidi, Zudan (Jurnal Membaca Bahasa dan Sastra Indonesia, 2023)
Islamic Defenders Front (FPI) vis-a-vis Government: Text and Context  of FPI’s Resistance DiscourseThis research discusses about how the form of FPI’s resistance toward the government through text and context that produced. This research used qualitative research by critical discourse analysis approach. Aspects of this approach are microstructural, mesostructural and macrostructural. There are some results of this research. First is microstruktural aspect. It is found that diction that used are eufimistic that have satirize meaning. Besides, formal diction  also used in the case of law,economic and culture. Second is the dimension that relates the process of producing and consuming the text (mesostructural). In this dimension, the texts are produced by the speakers who are ex-official of Islamic Defender Front. They are Habib Rizieq Shihab, Munarman, Novel Bamukmin and,  Aziz Yanuar. Background knowledge of the writers gave impact to the texts that are produced. Third is the dimension that relates the context outside the text (macrostructural). This dimension analyzes the text based on situational, institutional and social based on outside the text that give effect of the producing of text. Keywords: Text, Context, FPI, Government